An evidence-based chiropractic clinical decision aid for managing low back pain: results of a consensus process study - Vining, RD (J Manipulative Physiol Ther, 2019)
OBJECTIVE: The purpose of this study was to develop a clinical decision aid for chiropractic management of common conditions causing low back pain (LBP) in Veterans receiving treatment in U.S. Veterans Affairs (VA) healthcare facilities. METHODS: A consensus study using an online, modified Delphi technique and Research Electronic Data Capture (REDCap) web application was conducted among VA doctors of chiropractic (DCs). Investigators reviewed the scientific literature pertaining to diagnosis and treatment of non-surgical, neuromusculoskeletal LBP. Thirty seed statements summarizing evidence for chiropractic management, a graphical stepped management tool outlining diagnosis-informed treatment approaches, and support materials were then reviewed by an expert advisory committee. Email notifications invited 113 VA chiropractic clinicians to participate as Delphi panelists. Panelists rated the appropriateness of the seed statements and the stepped process on a 1-9 scale using the RAND/UCLA methodology. Statements were accepted when both the median rating and 80% of all ratings occurred within the highly appropriate range. RESULTS: Thirty-nine panelists (74% male) with a mean (SD) age of 46 (11) years and clinical experience of 17 (11) years participated in the study. Accepted statements addressed: 1) essential components of chiropractic care; 2) treatments for conditions causing or contributing to low back pain; 3) spinal manipulation mechanisms; 4) descriptions and mechanisms of commonly used chiropractic interventions, and 5) a graphical stepped clinical management tool. DISCUSSION: This study developed a chiropractic clinical decision aid for LBP management, which can be used to support evidence-based care decisions for veterans with LBP.